IPCAS: a direct‐method‐based pipeline from phasing to model building and refinement for macromolecular structure determination. Issue 1 (18th December 2019) - Ding, Wei; Zhang, Tao; He, Yao; Wang, Jiawei; Wu, Lijie; Han, Pu; Zheng, Chaode; Gu, Yuanxin; Zeng, Lingxiao; Hao, Quan; Fan, Haifu
Abstract : The pipeline IPCAS ( Iterative Protein Crystal structure Automatic Solution ) integrates the direct‐method program OASIS and other protein crystallography programs for experimental phasing and model building, with emphasis on direct‐method single‐wavelength anomalous diffraction/single isomorphous replacement phasing and direct‐method‐aided partial‐structure extension. Abstract : A new version (2.0) of the pipeline IPCAS ( Iterative Protein Crystal structure Automatic Solution ) has been released, in which the program OASIS performs direct‐method single‐wavelength anomalous diffraction/single isomorphous replacement phasing and direct‐method‐aided partial‐structure extension. IPCAS incorporates the widely used packages CCP4 and PHENIX for locating heavy atoms, density modification, molecular replacement, model building and refinement. Important extensions to the previous version of IPCAS include a resolution screening method for non‐crystallographic symmetry searching, an alternate model‐building protocol for avoiding premature convergence and direct‐method image processing for electron microscopy maps, including single‐particle cryo‐EM maps. Moreover, a new graphical user interface is provided for controlling and real‐time monitoring of the whole dual‐space iterative process, which works as a plugin to CCP4i . Applications of the new IPCAS to difficult cases have yielded promising results, including `direct‐method phasing and fragment extension' from weak anomalous diffraction signal data and `direct‐method‐aided partial‐structure extension' from low‐homology models.